PEMANFAATAN JERAMI DAN BUAH LONTAR SEBAGAI SUBSTRAT MENGGUNAKAN TEKNOLOGI MICROBIAL FUEL CELL - Basmanto, Basmanto; Sapitriani, Hernita; jusman, Nurfadhilah; Sahara, Sahara; Agus, Jasdar (JFT: Jurnal Fisika dan Terapannya, 2021)
The increasing energy consumption is not directly proportional to the availability of energy. This encourages the continued development of alternative energy sources to replace fossil energy sources.  In this research, a Microbial Fuel Cell (MFC) will be made as an alternative energy source that metabolism of bacteria to produce electrical energy.  Microbial Fuel Cell (MFC) is made by varying the type of substrate.  The type of substrate used is made of straw and borassus fruit extract. In this study, the MFC design uses a dual-chamber system consisting of an anode compartment and a cathode compartment. Analysis of the effect of substrate variations on MFC performance can be seen from the measurement data of current and voltage using a digital multimeter based on the length of time working with the addition of resistance and without resistance which is used to determine the power density value. The measurement results showed that the highest power density for straw substrate was obtained at 1st hour measurement, which a value of 770.1 mW/m2 for the addition of external resistance and 401.6 mW/m2 without external resistance.  Meanwhile, for the borassus fruit extract substrate, the highest power density was obtained at 29 hours of 594.1 mW/m2 using external resistance and 364.9 mW/m2 without external resistance. The resulting power density value is higher than previous studies so that the straw and borassus fruit extract substrate has a great potential to be used as a substrate in MFC technology.